TINJAUAN TENTANG KONDISI FISIK PESILAT PADA PERGURUAN HIMPUNAN SENI SILAT SELURUH INDONESIA (HIMSSI) DI KECAMATAN BENAI - Miki Marwilis SM Marwilis SM; Slamet '; Yuherdi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:The purpose of this study was to determine the physical condition Pesilat In College Art Association of Indonesian Silat (HIMSSI) in District Benai. Based on the results of field observations. In doing these basic movements needed a good physical condition, but based on observations by the author, the physical condition of the fighter should be improved as a fighter at a time when training too quickly feel tired.When viewed from the formulation of the problem, the type of research is descriptive quantitative. The population in this study was a fighter on martial arts community colleges throughout Indonesia (HIMSSI) in District Benai totaling 64 people. Because the population will be less rigorous than 64 people. The sampling technique used was purposive sampling.The author will take the entire population being sampled as many as 14 people. To obtain research data used TKJI test.Based on the analysis can be seen a review of physical condition fighters son in College Art Association of Indonesian Silat (HIMSSI) In Sub Benai of test of the average overall results of the physical condition of athletes at 15:29 with the medium category. Further review the physical condition fighters daughter at College Art Association of Indonesian Silat (HIMSSI) In District Benai of the average overall results of the physical condition of athletes at 14:29 with the medium category. Keywords: Overview of the Physical Condition